Comparison of spatula and cervex brush as a pap smear instrument in cervical cancer screening - Fang Fang
The incidence and mortality of cervical cancer has been decreasing sharply in the world because of regular cervix check-up and Pap smear test. But cervical cancer is still a main cause of cancer mortality in females, especially in developing countries. Pap smear test is known as a technique to screen cervical cancer and its precursors. The false negative results due to sampling error are the main reasons affecting the accuracy of Pap test. There are many new cervicovaginal cell specimen-collecting techniques developed to overcome the limitation of and to improve the accuracy of the Pap test. However, they pose a controversial issue because of the lack of concurrent and consistent gold standard, or different study populations, or wide range of lesions in published studies, making it difficult to compare these different cervical collecting procedures/techniques with Pap test, in terms of cervix cancer screening accuracy.This study: a) compares the Spatula and the Cervex brush in terms of smear specimen quality and endocervical cell recovery rate; and b) compares the spatula and the Cervex brush in terms of each corresponding Pap smear test characteristics as a screening test (sensitivity, specificity, likelihood ratio and predictive values) for cervix cancer and its precursors, with cervix biopsy histology as the gold standard.This is a screening validity study with RCT research design, comparing the spatula versus the Cervex brush in collecting cervix specimen for Pap smear cytology, with cervix biopsy histology as the gold standard. The study was carried out in Guanyang, Sichuan province, China, wherein the cervical cancer prevalence was 700-1400/100000. The participants were all women, 30 or more years of age, who fulfilled the inclusion and exclusion criteria and who gave their informed consent. The outcomes were estimated at a 95 confidence level of means, proportions and rates. Sensitivity, specificity, predictive values and likelihood ratios of the two groups were calculated with the formula of diagnostic test based on 2x2 tables. Independent t-test, chi-square test and Fisher's exact test were used to analyze the difference of means and proportions or rates between the spatula and Cervex brush groups.Among the 620 participants, there were 292 in the spatula group and 328 in the Cervex brush group. The baseline characteristics of the two groups were comparable. There were three cervical cancer-in-situ, five invasive cervical cancers and 93 CIN cases. The prevalence of cervical cancer was 1.290 (8/620) (95 CI 0.6021-2.6308). The prevalence of cervical cancer and its precancerous lesions was 16.3 (95 CI 14.2-18.4). There was no significant difference in the Pap specimen quality between the two groups, but the endocervical cell recovery rate was higher in the Cervex brush group (78.05) than in the spatula group (47.9) (P0.0001), regardless of menstrual status and cervical status. In the spatula group, it was demonstrated that endocervical cell recovery was directly related with detection of cervical cancer and its precancerous lesions. The sensitivity (31.03) in slides with endocervical cell recovery was higher, compared to those without endocervical cell recovery (4.35) (PCervex brush as a collector for Pap test can get 30 more smear specimen with endocervical cells compared to spatula. There was no significant difference (power of study = 0.13-0.26) between the two groups in terms of Pap smear specimen quality and the diagnostic accuracy of Pap smear test, particularly the sensitivity. The power of this study to detect a difference of 3 in sensitivity (spatula: 19.23 vs. Cervex brush: 22.22) is 26.